Implementation of Inclusive Education Practices for Children with Disabilities and Other Special Needs in Uganda - Okech, John Baptist; Yuwono, Imam; Abdu, Wamaungo Juma (Journal of Education and e-Learning Research, 2021)
This study aimed to assess the factors that influence the effective implementation of inclusive education, taking into consideration learners with disabilities and other special needs. The study objectives focused on the following key aspects that directly influence the implementation of inclusive education: inclusive policies, attitudes, perceptions, curriculum issues, and learning environment. The study adopted a case study design and employed qualitative approaches in sampling. Participants of the study (N=103) included special needs teachers (N=73) and learners with disabilities (N=30). Data collection was carried out through interviews. Some of the findings were positive, namely the policies on inclusive education were reported to be clear and well-suited to guiding the implementation practice, although some stakeholders were reported to be less committed. Attitudes towards learners with disabilities and other special needs were reported to be increasingly positive in the last decade. The findings on the perceptions of the ability and capability of learners with disabilities and other special needs to benefit from inclusive education drew a mixed reaction – some respondents reported that there were learners who were able to benefit from inclusive settings, while others were not. On the subject of the curriculum, the results revealed that some learners with disabilities and other special needs were capable of benefiting from the regular curriculum, while others would benefit from a special curriculum. Lastly, with regards to environmental factors, the study revealed that adequate preparations were always made to provide a conducive environment for learning in inclusive education settings. A major recommendation was made to draw the attention of policy makers to support inclusive education, which ought to be treated as a right and not a privilege for learners with disabilities and other special needs.